Understanding Sexual Dysfunctions in Individuals with Intellectual Disabilities from A Psychological Perspective - Spytska, Liana (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: This article delves into the complex world of sexual dysfunctions in individuals with intellectual disabilities (ID), a topic that has been relatively underexplored in the realm of psychological research. Intending to shed light on the unique challenges faced by this population, the article meticulously examines the barriers to effective communication, cognitive differences, and the social dynamics that impact both the experiences and treatment outcomes for individuals with ID. Methods: The study utilized a blend of empirical methods, including questionnaires, psychodiagnostic tests, and graphical representations of data, and was conducted among a substantial sample of 1450 individuals with ID in Kyiv, Ukraine. It offers a comprehensive overview of the sexual health landscape within this community. Results: The research findings highlight a notable prevalence of sexual dysfunctions among the ID population, exacerbated by a lack of accessible sexual education, the prevalence of unsafe sexual practices, and a high rate of self-reported sexual abuse. Conclusions: The article emphasizes the importance of a nuanced understanding and approach to sexual health care and education for individuals with ID. It calls for policies, practices, and further research that honor the dignity, autonomy, and sexual rights of individuals with ID, aiming to bridge the current gaps in care and understanding. By doing so, it contributes significantly to the discourse on sexual health in the ID population, offering valuable insights and directions for future work in this vital area of study.